Clinical Utility of Various Formulations of Calcipotriene and Betamethasone Dipropionate for the Treatment of Plaque Psoriasis in Patients Aged 12 Years or Older - Kędra K; Reich A (Drug Design, Development and Therapy)
Kamila Kędra,1,2 Adam Reich1 1Department of Dermatology, Institute of Medical Sciences, Medical College of Rzeszow University, Rzeszów, 35-055, Poland; 2Doctoral School, University of Rzeszow, Rzeszow, PolandCorrespondence: Adam Reich, Email adamandrzejreich@gmail.comAbstract: Plaque-type psoriasis is a chronic immune-mediated inflammatory skin disease of uncertain etiology, significantly impacting patient well-being. This chronic condition not only contributes to stigmatization and mental health challenges but also poses an independent risk for cardiovascular and other comorbid diseases. Affecting approximately 60 million people globally, psoriasis manifests primarily as mild-to-moderate disease in about 80% of cases, where topical therapy is pivotal. The most commonly used topical antipsoriatic therapy involves a combination of vitamin D3 analog (calcipotriene – Cal) and a synthetic potent corticosteroid (betamethasone dipropionate – BD). Various formulations of Cal/BD, including ointment, gel (topical suspension), and aerosol foam, have been approved by the US Food and Drug Administration (FDA). The cream based on the PAD (Polyaphron Dispersion) technology is another formulation of this combination drug, expanding the therapeutic options for patients with psoriasis. This article summarizes the most relevant published studies concerning the efficacy and safety of different calcipotriol and betamethasone formulations treating of plaque-type psoriasis in patients aged 12 or older.Keywords: psoriasis vulgaris, calcipotriene, betamethasone dipropionate, topical therapy, vitamin D derivatives, corticosteroids